2019
DOI: 10.1152/ajprenal.00621.2018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disruption ofNpr1depletes regulatory T cells and provokes high levels of proinflammatory cytokines and fibrosis in the kidneys of female mutant mice

Abstract: The present study was designed to determine the effects of gene knockout of guanylyl cyclase/natriuretic peptide receptor-A (GC-A/NPRA) on immunogenic responses affecting kidney function and blood pressure (BP) in Npr1 (coding for GC-A/NPRA)-null mutant mice. We used female Npr1 gene-disrupted ( Npr1−/−, 0 copy), heterozygous ( Npr1+/−, 1 copy), wild-type ( Npr1+/+, 2 copy), and gene-duplicated ( Npr1++/++, 4 copy) mice. Expression levels of Toll-like receptor (TLR)2/TLR4 mRNA were increased 4- to 5-fold in 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 116 publications
(160 reference statements)
3
17
1
Order By: Relevance
“…In the present studies, we observed the infiltration of monocyte/macrophage using the histological evaluation, which indicated a significant higher levels of these inflammatory cells in 0‐copy mice and also in the inhibitor‐treated 2‐copy and 4‐copy animals. These present findings are in direct relationship with our previous reports, indicating that the significant infiltration of monocyte/macrophage contribute to the inflammatory molecules in the kidneys 10,81 . The absence of pathological findings, together with low SBP and higher basal cGK/cGMP levels in 2‐copy + Rp, 4‐copy + Rp,, and 4‐copy + A71915 mice, confirmed the observation that low SBP and high cGK/cGMP levels have counter‐regulatory effects against the incidence of renal hypertrophy and fibrosis in inhibitor‐treated animals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present studies, we observed the infiltration of monocyte/macrophage using the histological evaluation, which indicated a significant higher levels of these inflammatory cells in 0‐copy mice and also in the inhibitor‐treated 2‐copy and 4‐copy animals. These present findings are in direct relationship with our previous reports, indicating that the significant infiltration of monocyte/macrophage contribute to the inflammatory molecules in the kidneys 10,81 . The absence of pathological findings, together with low SBP and higher basal cGK/cGMP levels in 2‐copy + Rp, 4‐copy + Rp,, and 4‐copy + A71915 mice, confirmed the observation that low SBP and high cGK/cGMP levels have counter‐regulatory effects against the incidence of renal hypertrophy and fibrosis in inhibitor‐treated animals.…”
Section: Discussionsupporting
confidence: 92%
“…Earlier, we found that renal transcription of the pro‐inflammatory cytokines was significantly increased in the absence of cGK/cGMP signaling in Npr1 0‐copy mice 5,11,13 . We also showed that the depletion of cGMP was associated with increased mRNA expression of pro‐inflammatory cytokine in 0‐copy mice 11,81 . Similarly, the present results demonstrate depleted renal cGMP levels, which seem to be associated with decreased cGK protein expression and activity in the kidneys of Npr1 0‐copy mice and 2‐copy and 4‐copy mice treated with Rp and A71915, leading to the renal hypertrophy, fibrosis, and renal dysfunction (Figure 7).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Studies with Npr1 (encoding NPRA) gene-knockout mice have demonstrated that a deficiency in NPRA increases BP by 35–45 mmHg and causes renal, vascular, and cardiac dysfunction that leads to hypertensive heart disease in mice, much like that observed in untreated hypertensive patients [64,65,66,67,68,69]. On the other hand, increased expression (gene-duplication) of NPRA in mice significantly reduces BP and increases second-messenger cGMP corresponding to the level of Npr1 gene copy number in both male and female mice [70,71,72,73,74,75,76,77].…”
Section: Historical Perspectives and Backgroundmentioning
confidence: 99%
“…Proinflammatory cytokines play a central role in the development of hypertension, cardiac hypertrophy, and CHF in experimental animal models and in humans ( Hirota et al, 1995 ; Testa et al, 1996 ; Vanderheyden et al, 2005 ; Vellaichamy et al, 2005a , 2014 ; Das et al, 2010 , 2020 ; Subramanian et al, 2016 ; Gogulamudi et al, 2019 ). Elevated circulating and myocardial levels of proinflammatory cytokines, including tumor necrosis factor (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) have been reported in the plasma of cardiomyopathic patients, correlating with the severity of their disease ( Testa et al, 1996 ; Vanderheyden et al, 2005 ).…”
Section: Nps and Their Receptors In Cardiovascular Disordersmentioning
confidence: 99%